Waste lithium ion battery graphite low-temperature homogeneous regeneration method

By introducing magnetic metal into the graphite of waste lithium-ion batteries and performing low-temperature calcination repair, and then removing magnetic metal through magnetic separation, the problems of poor regeneration performance and high energy consumption in the prior art are solved, and efficient and low-energy-consuming graphite regeneration is achieved. The obtained recycled graphite materials are suitable for commercial applications.

CN119706827AActive Publication Date: 2025-03-28CENT SOUTH UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411885139.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing graphite regeneration technology of used lithium-ion batteries has problems of poor performance, high energy consumption and uneven performance.

Method used

By introducing magnetic metal into waste graphite, and using compaction treatment to make the magnetic metal in close contact with graphite, low-temperature calcination is carried out to induce low-temperature repair of graphite and defect sites near the surface, and then removing the magnetic metal through magnetic separation to obtain regenerated graphite material.

Benefits of technology

The short process and low energy consumption regeneration of waste graphite are realized. The obtained recycled graphite material has good rate performance and high capacity. It also removes magnetic metals through magnetic separation, which improves the purity of the material and is suitable for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706827A_ABST
    Figure CN119706827A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature homogeneous regeneration method of waste lithium ion battery graphite, which comprises the following steps: carrying out ball-milling mixing on magnetic metal and waste graphite, compacting, and carrying out low-temperature calcination in an inert atmosphere to obtain a primarily repaired graphite material; and grinding the primarily repaired graphite material again, dispersing the primarily repaired graphite material in a solution, and performing magnetic separation to remove the magnetic metal, thereby obtaining the regenerated graphite material. The low-temperature repair of the graphite and the defect sites near the surface can be induced when the magnetic metal is in close contact with the graphite, the obtained regenerated graphite material is good in electrochemical performance, the magnetic metal can be removed through magnetic separation, and the purity of the regenerated graphite material is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-temperature homogeneous regeneration method for waste lithium-ion battery graphite, belonging to the technical field of waste battery recycling. Background Art

[0002] Graphite is a strategic mineral resource in my country and plays a pillar role in my country's national economy. At present, graphite resources have been successfully used as negative electrode materials for lithium-ion batteries. With the rapid development of the new energy industry, lithium-ion batteries have been widely used in various industries in my country. However, due to the limited life of lithium-ion batteries, lithium-ion batteries will inevitably become scrapped. Facing the massive wave of waste batteries, opening up the high-quality recycling link of waste batteries is a key step in realizing the last link of the closed-loop cycle of the new energy industry.

[0003] At present, the recycling of graphite negative electrodes for lithium-ion batteries is divided into wet recycling and direct regeneration. Among them, wet recycling is to extract the key metal elements inside through reagents such as acids and alkalis, and then the participating graphite waste is piled up; at present, most of the waste treated by wet processing serves as fuel and is incinerated, resulting in a large waste of resources; while direct regeneration requires long-term high-temperature calcination at 2800°C to repair the graphite crystal phase. Although direct regeneration has high efficiency in graphite resource utilization, problems such as high energy consumption and high pollution have resulted in low economic value of graphite recycling, and most direct regeneration companies do not carry out the repair and production of waste graphite. In addition, the damage of waste graphite materials from different sources is different, and simple repair cannot induce uniform repair of graphite, resulting in uneven performance of regenerated graphite, which ultimately leads to the production of regenerated graphite entering the commercial market.

[0004] Chinese patent CN117954725A discloses a method of mixing waste lithium-ion battery graphite negative electrode material with ammonium salt-strong base composite salt, calcining, washing and drying in sequence to obtain a precursor material; the precursor material is then mixed with a low-boiling point organic metal salt-energy storage anion powder composite for vacuum calcination to obtain high-value regenerated graphite. This method can effectively achieve the capacity repair of graphite negative electrode materials, but the method will change the internal structure of the graphite material through strong alkali and high-temperature etching in the early stage, and the repair of the charge and discharge capacity performance of the graphite electrode material depends on the introduction of metal ions to form a combination with sulfur atoms or selenium atoms to form a high-capacity electrode material transition metal sulfur-selenium compound, that is, some magnetic substances that cannot be removed will be introduced during the repair, which will also have an adverse effect on the commercial circulation of lithium battery graphite negative electrode materials. Summary of the invention

[0005] In view of the problems of poor regeneration performance, high energy consumption, and uneven performance of existing waste graphite, the purpose of the present invention is to provide a low-temperature homogeneous regeneration method for waste lithium-ion battery graphite. The method introduces magnetic metal into waste graphite and performs compaction treatment, and utilizes the close contact between magnetic metal and graphite to induce low-temperature repair of defect sites in graphite and near the surface, thereby achieving short-process and low-energy regeneration of waste graphite, and the obtained regenerated graphite material has good rate performance and high capacity.

[0006] In order to achieve the above technical objectives, the present invention provides a low-temperature homogeneous regeneration method for waste lithium-ion battery graphite. The method comprises the following steps: mixing magnetic metal with waste graphite by ball milling and compacting, and then calcining at low temperature under an inert atmosphere to obtain a preliminary repaired graphite material; the preliminary repaired graphite material is ground again and dispersed in a solution, and then the magnetic metal is removed by magnetic separation to obtain a regenerated graphite material.

[0007] In the technical solution of the present invention, compaction treatment is the prerequisite for repair, and the introduction of magnetic metal is the key to repair. Specifically, the present invention can induce low-temperature repair of graphite and near-surface defect sites by introducing magnetic metals. The principle is: first, magnetic metals have a special electronic structure. When in close contact with graphite, free electrons in magnetic metals can migrate to the defect sites of graphite to fill the electron loss, stabilize the structure of graphite, and promote the repair of defects; second, magnetic metals will generate local electric fields near the graphite surface. For defects caused by processes such as lithium ion deintercalation, the local electric field helps to adjust the arrangement of atoms and promote the gradual healing of defects; third, magnetic metals can play an effective catalytic role on the graphite surface, which can reduce the activation energy of the reaction, thereby achieving repair at low temperatures. The catalytic effect of magnetic metals on waste graphite depends on the contact degree between waste graphite and magnetic metals. If there is no contact, the catalytic effect formed by the interface is difficult to complete. In addition, some graphite that has not been contacted cannot be repaired, resulting in incomplete repair effects. The present invention can significantly improve the contact between waste graphite and magnetic materials through compaction treatment, improve the surface and interface repair effect of waste graphite, and finally achieve low-temperature homogeneous repair of waste graphite. Compared with the prior art, the repaired graphite material of the present invention can be removed by magnetic separation, and the purity of the regenerated graphite material is further improved without affecting the capacity and performance of the repaired graphite material, thereby realizing its commercial application.

[0008] The inventors found that the present invention uses magnetic metals compared to magnetic metal salts (magnetic metal ions), and the particle size is larger, which is conducive to the magnetic separation of the rear end, and avoids the generation of waste acid and waste liquid. If the magnetic metal is replaced with the corresponding metal salt, the metal salt will produce inhomogeneous metal element particles due to decomposition and reduction during the calcination process, and some particles with smaller scales cannot be separated by magnetic separation and remain in the regenerated graphite material, and can only be washed by acid, and secondary damage will be caused to the regenerated graphite material by acid washing. In addition, the traditional metal salt catalytic process may introduce anions that are difficult to wash during the regeneration process, while the organic metal salt will introduce organic carbon chains that can decompose amorphous carbon, which ultimately leads to a decrease in the yield of the material and an increase in electrochemical side reactions. The large-sized magnetic particles in the present invention help the carbon particles on the graphite surface to migrate under low temperature conditions, fill the defects on the surface of the failed graphite particles, provide pre-embedded interlayer spacing for lithium ion storage, and improve the capacity and rate performance of the material.

[0009] As a preferred solution, the waste graphite comes from waste lithium-ion batteries, pole pieces, unfilled lithium-ion batteries, etc. purchased on the market.

[0010] As a preferred solution, the magnetic metal is at least one of cobalt, nickel and iron.

[0011] As a preferred solution, the mass ratio of the magnetic metal to the waste graphite is (0.1-10): 1. The mass ratio of the magnetic metal to the waste graphite has a direct impact on the graphite repair effect. If the mass ratio is too low and the magnetic metal content is too little, it is difficult to provide enough active sites for the waste graphite and it is impossible to induce the near-surface of the waste graphite to achieve uniform repair at low temperature; and if the mass ratio is too high and the magnetic metal content is too high, not only will the processing cost increase and the thermal energy utilization be seriously insufficient, but it will also increase the difficulty of subsequent magnetic separation to remove the magnetic metal, and even lead to a decrease in the purity of the regenerated graphite material.

[0012] As a preferred solution, the magnetic metal is a powder with a D50 of 0.1 μm to 200 μm. If the D50 of the magnetic metal is too small, the particle size is small, the metal powder is highly active, and it is easy to spontaneously combust in the air, which is not conducive to production and preparation, and it is difficult to completely remove it through subsequent magnetic separation; if the D50 of the magnetic metal is too large, the particle size is large, and it is difficult for the magnetic metal to form a close and uniform contact with the waste graphite, making it difficult to achieve near-surface homogeneous repair of the waste graphite.

[0013] As a preferred solution, the compaction pressure is 10-100 MPa. If the pressure is too low during the compaction process, it is difficult for the waste graphite to form a close contact with the magnetic metal, reducing the homogeneous repair effect; if the pressure is too high, the waste graphite will be damaged during the compaction process, and the overall structure of the graphite will be damaged. At the same time, the mixed material after severe compaction is difficult to grind and disperse, making it difficult to remove the magnetic metal later.

[0014] As a preferred solution, the low-temperature calcination atmosphere is one of argon, hydrogen and a hydrogen-argon mixture.

[0015] As a preferred solution, the conditions for low-temperature calcination are: temperature of 500-1500°C and time of 1-20 hours. If the calcination temperature is too low or the calcination time is too short, the activity of the magnetic metal and the mobility of carbon atoms in the graphite are difficult to be fully stimulated, making it difficult to repair defects. If the calcination temperature is too high, the magnetic metal melts and aggregates, and the induced repair effect cannot be achieved.

[0016] As a preferred solution, the solution contains at least one dispersant selected from CMC (carboxymethyl cellulose), ethanol and sodium dodecylbenzene cyclopentane, and the mass ratio between the dispersant and the preliminary repaired graphite material is 1g: (10-1)kg. The present invention forms a tight connection between the material and the graphite after compaction treatment. If it is only simply crushed, the agglomerates formed by some magnetic metals and graphite are difficult to dissociate, and some magnetic particles may remain in the repaired graphite, resulting in the repaired graphite having too high a magnetic substance content, which is difficult to meet commercial application standards. Therefore, the graphite is dispersed in an aqueous solution to increase the degree of dissociation of the graphite material. In addition, the surface hydrophobicity of graphite is strong, and it is difficult to disperse the graphite material in the aqueous solution when it is directly placed in the aqueous solution. Therefore, the present invention adds an appropriate amount of dispersant to promote the dispersion and dissociation of graphite particles in the aqueous phase.

[0017] As a preferred solution, the magnetic separation adopts a wet magnetic separator, the magnetic separation intensity is 0.5T to 2.0T, and the cycle is 3 to 6 times. Within the selected magnetic separation intensity range, the removal effect of the magnetic metal introduced into the initial repaired graphite material can be guaranteed, and through multiple cycles, the magnetic metal can be removed more thoroughly to ensure the quality of the regenerated graphite material.

[0018] As a preferred solution, the content of magnetic metal powder in the regenerated graphite material is less than 50 ppm.

[0019] The ball milling process involved in the present invention is a conventional operation process in the prior art, and its purpose is to convert the mixed material after compaction and sintering into powder to facilitate the next step of dispersion and magnetic separation.

[0020] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0021] 1) The waste graphite regeneration process provided by the present invention is simple, has a short process flow and low energy consumption, and the method is simple to operate, has a short cycle and high economic benefits.

[0022] 2) The present invention introduces magnetic metal into waste graphite and performs compaction treatment. When the magnetic metal is in close contact with the graphite, it can induce low-temperature repair of defect sites in the graphite and near the surface. The obtained regenerated graphite material has good electrochemical properties, and the magnetic metal can be removed by magnetic separation, further improving the purity of the regenerated graphite material.

[0023] 3) The method of the present invention can achieve homogeneous regeneration of different types of waste graphite. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 These are the electrochemical performance diagrams of three batches of graphite materials repaired by Example 5 of the present invention.

[0025] Figure 2 The electrochemical performance diagrams of three batches of graphite materials repaired by Example 1 of the present invention are shown.

[0026] Depend on Figure 1 and Figure 2 By comparison, it can be seen that by using the repair treatment combining the magnetic metal and compaction treatment of the present invention, the batch difference of the regenerated graphite material is small, and homogeneous regeneration can be achieved. DETAILED DESCRIPTION

[0027] The following examples are used to illustrate the present invention, but are not intended to limit the scope of protection of the claims of the present invention.

[0028] The waste graphite used in the present invention comes from waste batteries purchased on the market; the waste lithium-ion batteries are subjected to processes such as safe discharge, manual disassembly, and negative pressure drying to obtain relatively pure waste lithium-ion battery negative electrode sheets, and then subjected to processes such as multiple ultrasonic washing and drying to obtain waste lithium-ion battery graphite materials.

[0029] Through the treatment processes of magnetic metal, compaction treatment and magnetic separation in the embodiments of the present invention, the content of magnetic metal powder in the obtained regenerated graphite material is less than 50 ppm.

[0030] In the embodiment of the present invention, the volume ratio of the dispersant to water in the aqueous solution containing the dispersant is 1:1, and the mass ratio of the dispersant to the preliminary repaired graphite material is 0.001g:1g.

[0031] Example 1 (Comparative Example)

[0032] 1g of waste graphite powder is placed in a press for compaction at a pressure of 20MPa. The compacted material is placed in a tubular furnace and calcined at 800℃ for 10h in a nitrogen atmosphere, and then cooled naturally to obtain recycled graphite material.

[0033] Example 2 (Comparative Example)

[0034] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then put into a ball mill for ball milling and mixing. The mixed material is calcined at 800℃ for 10h in a nitrogen atmosphere, and then cooled naturally. The cooled material is put into the ball mill again for grinding, and the ground material is dispersed in an aqueous solution containing ethanol. Magnetic separation is performed using a wet magnetic separator with a magnetic separation intensity of 1.0T and 5 magnetic separation times. The material after magnetic separation is dried to obtain recycled graphite material.

[0035] Example 3 (Comparative Example)

[0036] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is magnetically separated using a dry magnetic separator with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain recycled graphite material.

[0037] Example 4 (Comparative Example)

[0038] The magnetic metal powder (D50, 10μm) and waste graphite were weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then put into a ball mill for ball milling and mixing. The mixed powder was compacted under a press with a pressure of 20MPa. A wet magnetic separator was used for magnetic separation (the dispersant was ethanol aqueous solution), the magnetic separation intensity was 1.0T, the number of magnetic separations was 5, and the material after magnetic separation was dried to obtain recycled graphite material.

[0039] Example 5

[0040] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0041] Example 6

[0042] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (nickel is 2g, graphite is 1g), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800℃ for 10h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0043] Example 7

[0044] The magnetic metal powder (D50, 0.1μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0045] Example 8

[0046] The magnetic metal powder (D50, 200μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800℃ for 10h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0047] Example 9

[0048] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 0.1:1 (0.1g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0049] Example 10

[0050] The magnetic metal powder (D50, 10μm) and the waste graphite are weighed at a mass ratio of 10:1 (10g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0051] Embodiment 11

[0052] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 10MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0053] Example 12

[0054] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 100MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0055] Example 13

[0056] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in an argon atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0057] Embodiment 14

[0058] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 500°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0059] Embodiment 15

[0060] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 1500°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0061] Example 16

[0062] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 1h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0063] Embodiment 17

[0064] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 20h in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0065] Embodiment 18

[0066] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing CMC. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain recycled graphite material.

[0067] Embodiment 19

[0068] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 0.5T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0069] Embodiment 20

[0070] The magnetic metal powder (D50, 10μm) and waste graphite are weighed in a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 2.0T and a number of magnetic separations of 5 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0071] Embodiment 21

[0072] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and a number of magnetic separations of 3 times. The material after magnetic separation is dried to obtain a regenerated graphite material.

[0073] Embodiment 22

[0074] The magnetic metal powder (D50, 10μm) and waste graphite are weighed at a mass ratio of 2:1 (2g of cobalt and 1g of graphite), and then placed in a ball mill for ball milling and mixing. The mixed powder is compacted under a press with a pressure of 20MPa. The pressed material is placed in a tubular furnace and calcined at 800°C for 10 hours in a nitrogen atmosphere, followed by natural cooling. The cooled material is placed in a ball mill for grinding again, and the ground material is dispersed in an aqueous solution containing ethanol. A wet magnetic separator is used for magnetic separation, with a magnetic separation intensity of 1.0T and 6 magnetic separation times. The material after magnetic separation is dried to obtain recycled graphite material.

[0075] The regenerated graphite materials of Examples 1 to 22 were tested according to the following method. The results are shown in Table 1.

[0076] 1) Sample preparation

[0077] In each embodiment, the waste graphite comes from waste batteries purchased on the market. The recycled material, acetylene black, and sodium hydroxymethyl cellulose (CMC) are added with a certain amount of deionized water in a mass ratio of 8 / 1 / 1 to prepare a uniform slurry. The obtained slurry is coated on a copper foil and then placed in a vacuum oven at 100°C for 24 hours for drying. The obtained pole piece is cut by a slicer into small discs with a diameter of 1 cm to become the obtained positive electrode material, wherein the copper foil is loaded with more than 1 mg of active substance.

[0078] The obtained positive electrode sheet, electrolyte, lithium sheet, battery shell, diaphragm, etc. are placed in an argon glove box for battery assembly. After sealing, the obtained battery is an assembled button battery.

[0079] Note: All examples adopt the above-mentioned electrode material preparation method.

[0080] 2) Test methods

[0081] After the button cell was left to stand for 12 hours, it was placed on the blue-electric test channel for electrochemical performance testing, where the current density was set to 1.0C, the voltage range was set to 0.01-2.5V, etc. The data obtained is the data directly displayed on the blue-electric tester, and can be directly taken.

[0082] Table 1 Electrochemical performance test results in each embodiment

[0083]

[0084]

[0085]

Claims

1. A low temperature homogeneous regeneration method for waste lithium ion battery graphite, characterized in that: The magnetic metal and waste graphite are ball-milled, mixed and compacted, and then placed in an inert atmosphere for low-temperature calcination to obtain a preliminary repaired graphite material; the preliminary repaired graphite material is ground again and dispersed in a solution, and the magnetic metal is removed by magnetic separation to obtain a regenerated graphite material.

2. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 1, characterized in that: The magnetic metal is at least one of cobalt, nickel and iron.

3. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 1 or 2, characterized in that: The mass ratio of the magnetic metal to the waste graphite is (0.1-10):

1.

4. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 3, characterized in that: The magnetic metal is powder with a D50 of 0.1 μm to 200 μm.

5. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 4, characterized in that: The compaction pressure is 10-100 MPa.

6. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 1, characterized in that: The conditions for the low-temperature calcination are: a temperature of 500 to 1500° C. and a time of 1 to 20 hours.

7. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 6, characterized in that: The solution contains at least one dispersant selected from the group consisting of CMC, ethanol and sodium dodecylbenzene ring acid, and the mass ratio of the dispersant to the preliminary repaired graphite material is 1 g: (10-1) kg.

8. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 7, characterized in that: The magnetic separation adopts a wet magnetic separator, the magnetic separation intensity is 0.5T to 2.0T, and the cycle is 3 to 6 times.

9. A low-temperature homogeneous regeneration method for waste lithium-ion battery graphite according to claim 1, characterized in that: The content of magnetic metal powder in the regenerated graphite material is less than 50 ppm.

Citation Information

Patent Citations

  • High-valued regeneration method for graphite negative electrode material of waste lithium ion battery

    CN117954725A

  • Self-repairing type high-nickel ternary lithium-battery electrode material with long service life and preparation method

    CN108376775A

  • Preparation method of efficient regenerated activated carbon

    CN111318254A

  • Preparation method of electromagnetic shielding self-repairing skin-friendly hydrogel

    CN113501976A

  • Structure repairing agent for regeneration and repair of recycled graphite negative electrode material of lithium ion battery and use method of structure repairing agent

    CN115084694A